Nanozeolites as support for laccase immobilization: Application to mediated glycerol oxidation - Miller, Alex Henrique [UNESP] (2021)
This study investigated the use of nanozeolites as support for laccases from P. ostreatus (LPO), Aspergillus sp (LAsp) and A. bisporus (LAB) immobilization applied to 2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO) mediated glycerol oxidation. Selected complexes led to up to 5% glycerol conversion, and interestingly, up to 100% selectivity to glyceraldehyde after 48 h. Free enzymes led to significantly higher yields (up to 82%) but lacked selectivity when tested under the same conditions. These findings suggest that laccases immobilized into nanozeolites are promising catalysts for the selective oxidation of glycerol. With the aim to understand the different behavior of free or immobilized enzymes, electron paramagnetic resonance (EPR) spectroscopy was applied. A significant shift of the T2 parallel copper hyperfine coupling constant was observed. This suggested a perturbation on the catalytic site after immobilization due to pH variation of the enzymatic microenvironments, thus influencing performance of laccase immobilized on nanozeolites.